Fifteen [compact disc] (Red House Records, 2017)
2017 release. Fifteen is the first recording in six years from contemporary folk's most popular group, The Wailin' Jennys. An entrancing collection of cover songs, it includes tunes by Tom Petty, Emmylou Harris and Dolly Parton, and is their first new music since 2011's acclaimed album, Bright Morning Stars. For founding members Nicky Mehta and Ruth Moody, along with longtime member Heather Masse, Fifteen celebrates a 15-year musical partnership that has resulted in four award-winning studio albums and one live recording on Red House Records, three of which landed the trio on the Billboard charts, while garnering the band a worldwide fanbase. All three band members sing and play a variety of instruments (acoustic guitar, accordion, banjo, ukulele) to create a shimmering tapestry of rich vocals and instrumentals. Additional musicians include Richard Moody (Ruth's brother), Sam Howard, Adrian Dolan and Adam Dobres. Produced by The Wailin' Jennys, Fifteen is a gorgeous feather in the cap of the band that has thrilled millions of listeners to A Prairie Home Companion radio ..."--Amazon.com.